Glycoprotein biosynthesis in small intestine: III. Enzymatic basis for the difference in the antigenicity of mucins - Kim, Young S. (1972)
Rat small intestinal mucosa was examined for ability to produce mucins with human blood group A, B, and H activity. Blood group activity of the mucins was compared to antigenic activity of red blood cells in individual rats and the enzymatic basis for differences was investigated. Red cells in all the rats examined contained human blood group A and B antigens. All rats synthesized intestinal mucins having B and H antigenic activity but 57% failed to produce mucins with blood group A activity (A(-)); the remaining 43% (A(+)) produced A substance. The activities of five glycosyltransferases including α(1→2) fucosyltransferase, the determinant of human secretor status, were measured in the intestine of A(+) and A(-) rats. Four enzymes were the same in both groups, while the fifth, N-acetylgalactosaminyltransferase, was present only in A(+) rats. The specificity of this latter enzyme, as found in the rat, appeared similar to that in humans, since it catalyzed addition of N-acetyl-D-galactosamine only to acceptors which had the H determinant structure. In the presence of the enzyme, A(-) mucin could be converted to A(+) mucin; this was shown both by hemagglutination inhibition and immunoprecipitin studies of the products of incubation of A(-) mucin with UDP-N-acetyl-D-galactosamine and the enzyme. These studies indicate that the difference between A(+) and A(-) rats is due to the apparent absence of N-acetylgalactosaminyltransferase in the intestinal mucosa of A(-) rats. These rats may provide experimental models for studies on the effect of ABO and secretor status on susceptibility to ulceration and carcinogenesis.